Molecular recognition in (+)-alpha-pinene oxidation by cytochrome P450cam. - Bell, S; Chen, X; Sowden, R; Xu, F; Williams, J; Wong, L; Rao, Z (2003)
Oxygenated derivatives of the monoterpene (+)-alpha-pinene are found in plant essential oils and used as fragrances and flavorings. (+)-alpha-Pinene is structurally related to (+)-camphor, the natural substrate of the heme monooxygenase cytochrome P450(cam) from Pseudomonas putida. The aim of the present work was to apply the current understanding of P450 substrate binding and catalysis to engineer P450(cam) for the selective oxidation of (+)-alpha-pinene. Consideration of the structures of (+)-camphor and (+)-alpha-pinene lead to active-site mutants containing combinations of the Y96F, F87A, F87L, F87W, and V247L mutations. All mutants showed greatly enhanced binding and rate of oxidation of (+)-alpha-pinene. Some mutants had tighter (+)-alpha-pinene binding than camphor binding by the wild-type. The most active was the Y96F/V247L mutant, with a (+)-alpha-pinene oxidation rate of 270 nmol (nmol of P450(cam))(-)(1) min(-)(1), which was 70% of the rate of camphor oxidation by wild-type P450(cam). Camphor is oxidized by wild-type P450(cam) exclusively to 5-exo-hydroxycamphor. If the gem dimethyl groups of (+)-alpha-pinene occupied similar positions to those found for camphor in the wild-type structure, (+)-cis-verbenol would be the dominant product. All P450(cam) enzymes studied gave (+)-cis-verbenol as the major product but with much reduced selectivity compared to camphor oxidation by the wild-type. (+)-Verbenone, (+)-myrtenol, and the (+)-alpha-pinene epoxides were among the minor products. The crystal structure of the Y96F/F87W/V247L mutant, the most selective of the P450(cam) mutants initially examined, was determined to provide further insight into P450(cam) substrate binding and catalysis. (+)-alpha-Pinene was bound in two orientations which were related by rotation of the molecule. One orientation was similar to that of camphor in the wild-type enzyme while the other was significantly different. Analysis of the enzyme/substrate contacts suggested rationalizations of the product distribution. In particular competition rather than cooperativity between the F87W and V247L mutations and substrate movement during catalysis were proposed to be major factors. The crystal structure lead to the introduction of the L244A mutation to increase the selectivity of pinene oxidation by further biasing the binding orientation toward that of camphor in the wild-type structure. The F87W/Y96F/L244A mutant gave 86% (+)-cis-verbenol and 5% (+)-verbenone. The Y96F/L244A/V247L mutant gave 55% (+)-cis-verbenol but interestingly also 32% (+)-verbenone, suggesting that it may be possible to engineer a P450(cam) mutant that could oxidize (+)-alpha-pinene directly to (+)-verbenone. Verbenol, verbenone, and myrtenol are naturally occurring plant fragrance and flavorings. The preparation of these compounds by selective enzymatic oxidation of (+)-alpha-pinene, which is readily available in large quantities, could have applications in synthesis. The results also show that the protein engineering of P450(cam) for high selectivity of substrate oxidation is more difficult than achieving high substrate turnover rates because of the subtle and dynamic nature of enzyme-substrate interactions.